Strategic Management of Resources for International Business Operations in Small Consulting Firms - People, Processes and Tools in Managing International operations - Lyaruu, Conrad (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Research on strategic management of resources for small consulting firms which are international or planning to operate internationally is scarce or not existing at all. It is however important to start generating the theories that will support managers in their decision making and planning. This thesis investigates how do small management consulting firms manage their internal and external resources while operating in international markets. Throughout the study, aspects related to internal and external resources management as well as management strategies in these firms have been examined in relations to firm’s internationalisation activities. A qualitative analysis was carried out whereby four small consulting firms in Export Management Consulting, Integration Services Consulting-, Software Development Consulting- and Business Solutions Consulting companies were interviewed. In order to generate the holistic understanding of the study, the thesis writer selected Value Enhanced Collaborative Working (VECW) model as an analysis framework. The model focuses on people, processes and tools as key elements that small consulting firms consider when thinking about managing their international operations. The findings of the thesis reveal that, internal and external resources in the interviewed consulting firms are viewed similarly, but managed differently depending on the nature and size of the firm. Firm’s management strategies concentrate on the adequate utilisation of the employees' motivation and experiences, effective stakeholders' management, various administrative evaluation processes and tools, the ability to realise useful networks, constant improvement through employee trainings, employees and customers’ feedbacks as well as enhanced freedom in order to support employees’ creativity. Further research to examine functional administrative tools and tools that small consulting firms could use to assess their resource capabilities when planning to become international would benefit the smaller businesses in terms of resources management and certainty in planning.